Nutrition Programs of Higher Education in the Occupied Palestinian Territories: A Descriptive Snapshot. Issue 2 (June 2022) - Mansour, Miral; Aboul-Enein, Basil H.; Salsa, Ghadir Helal; Benajiba, Nada
This report stresses the importance of promoting capacity building and training of nutritionists and dietitians as vital strategies in addressing nutrition-related health problems and improving health outcomes in the Occupied Palestinian Territories (OPT). Higher education institutions play a vital role in this process. The report identifies degree-granting nutrition programs available in OPT in both Arabic and English by carrying out an electronic review of universities and college websites, department web links, and academic program home pages. Out of the 52 accredited institutions in the OPT, 10 offered nutrition degree programs of which four are located in the Gaza Strip and six in the West Bank. Nutrition-affiliated programs included bachelor's degrees in nutrition sciences and public health, health nutrition, nutrition and food technology, nutrition and dietetics, therapeutic nutrition, and nutrition and food processing. Two universities offered a master's degree in clinical nutrition in addition to a bachelor's program. None of the selected educational institutions offered a doctoral degree program. The number of universities in OPT offering bachelor's degree in nutrition affiliated programs is relatively high as compared to neighboring Arab countries. Additional development of graduate programs to strengthen the dietetics/nutrition profession in OPT is warranted.